Apheresis in patients with sepsis: A multicenter retrospective study. (October 2021) - Aydin, Kaniye; Korkmaz, Serdal; Erkurt, Mehmet Ali; Sarici, Ahmet; Ekinci, Omer; Baysal, Nuran Ahu; Berber, Ilhami; Dogan, Ali; Dal, Mehmet Sinan; Giden, Asli Odabasi; Ulas, Turgay; Kuku, Irfan; et al.
Abstract: Background and objectives: To consider the effectiveness of apheresis, which is a supportive treatment method, in sepsis. Materials and methods: A hundred and eleven adults with sepsis or septic shock were included in this retrospective study. The demographic characteristics of the patients, the focus and source of infection causing sepsis or septic shock, characteristics of the pathogen, Acute Physiological and Chronic Health Assessment (APACHE) II score, routine laboratory values, which apheresis method was used, the characteristics of the replacement fluids used during the apheresis procedure, the number of apheresis procedures, complications related to the apheresis procedure, the follow-up time after the procedure, and mortality were recorded. The primary outcome was 28-day mortality. Results: Sixty-nine (62.2 %) of the patients were male. The mean age of the patients was 47.7 ± 18.6 years. The most common source of sepsis was hospital-acquired (79.3 %), the most common pathogen causing sepsis was gram-negative bacteria (41.4 %), and the most common infection site was the respiratory tract (58.7 %). The median APACHE II score was 19 (13−24). 92 (82.9 %) of the patients had septic shock. Theropeutic plasma exchange (TPE) was performed in 11.7 % of the patients and immunoabsorbtion IA in 88.3 %. The median number of sessions was 3 (3−5). No procedure-related fatal complication was observed in the study. While 28-day mortality was 61.3 % in all patients, when the mortality according to the apheresis procedures was examined, it was 11.3 % and 88.2 % in the patients who underwent TPE and IA, respectively. The most common cause of mortality was multiorgan failure. Conclusions: Apheresis in sepsis can be considered as a salvage treatment. The indication for apheresis in sepsis is still at the level of patient-based individualized decision in line with the studies done so far, including our study. However, there is a need for a multicenter randomized controlled study with a large number of patients in order to give positive or negative recommendations about its effectiveness.